Dinamika Psikologis Investor Ritel di Era Volatilitas Harga Emas Ekstrem: Eksplorasi Fenomena Fear of Missing Out (FOMO) dan Ilusi Safe-Haven pada Pengguna Aplikasi Emas Digital - Fitayantri Tamau; Siti Harwianti Santoso; Francisca Anggun Therok (ITB AAS Indonesia Surakarta, 2026)
Thi s stu d y e xami ne s the psychologi cal d ynami cs of re tai l i nve stors ami d e xtre me gold pri ce volati li ty, focu si ng on the e me rge nce of Fe ar of Mi ssi ng Ou t (FOMO) and the i llu si on of safe -have n among u se rs of d i gi tal gold savi ngs appli cati ons. The re se arch was moti vate d by the sharp e scalati on of gold pri ce s d u ri ng 2024–2026—from approxi mate ly U SD 2,040 pe r troy ou nce i n e arly 2024 to ove r U SD 5,176 pe r troy ou nce i n the fi rst qu arte r of 2026—alongsi d e the rapi d growth of fri cti onle ss d i gi tal i nve stme nt platforms i n I nd one si a. U si ng a qu ali tati ve d e scri pti ve approach wi th a phe nome nologi cal d e si gn, d ata we re colle cte d i n Manad o Ci ty throu gh i n-d e pth i nte rvi e ws, obse rvati on, and d ocu me ntati on i nvolvi ng le ctu re rs, stu d e nts, and me mbe rs of the ge ne ral pu bli c, se le cte d throu gh pu rposi ve sampli ng. D ata analysi s followe d the i nte racti ve mod e l of Mi le s, Hu be rman, and Sald ana, su pporte d by sou rce and te chni qu e tri angu lati on. The fi nd i ngs re ve al thre e pri nci pal conclu si ons: (1) the me ani ng of gold has shi fte d from a prote cti ve i nstru me nt to a spe cu lati ve asse t promi si ng rapi d capi tal gai ns; (2) i nve stme nt d e ci si ons we re pre d omi nantly d ri ve n by FOMO, he rd be havi or, anchori ng bi as, and cogni ti ve d i ssonance rathe r than fu nd ame ntal analysi s; and (3) the fri cti onle ss archi te ctu re of d i gi tal gold appli cati ons i nte nsi fi e d psychologi cal vu lne rabi li ty and faci li tate d i mpu lsi ve bu yi ng at ove rbou ght marke t cond i ti ons, re i nforci ng the safe -have n i llu si on. Keywords: be havi oral fi nance , FOMO, safe -have n, d i gi tal gold , re tai l i nve stor